The effects of using digital vocabulary journal in muet writing performance among pre-university students: An action research - Ting Pick Dew (Penerbit UMS, 2024)
In learning English as a second language, the importance of vocabulary competency has long been recognized for its significance. An area where vocabulary knowledge has demonstrated significant promise is in the realm of writing as the breadth and depth of students’ vocabulary are reflected in the general quality of their writing. Hence, the introduction of vocabulary journal is essential as it has been used to create interactive and immersive learning experiences that help learners acquire and retain new words more effectively. This classroom-based action research investigated the impacts of keeping digital vocabulary journal towards writing performance of ten pre-university students in a pre-university center in Sabah. It sought to to find out whether there is any difference in the students’ writing scores prior to and after keeping vocabulary journal as well as to assess the students' attitudes toward maintaining a digital vocabulary journal. This action research used a mixed-method approach. Pre-test and post-test writing scores comprised the study's quantitative component, while the qualitative approach used semi-structured interviews and product analysis. The results indicated significant difference with large effect size and positive students’ attitudes towards digital vocabulary journal. As a result, the assertions regarding the advantages of digital vocabulary journals were empirically supported by this action research study. By engaging in this type of research, teachers can gain valuable insights into how to optimize their use of digital vocabulary journal in the classroom, and ultimately improve the effectiveness of their teaching practice